2019
DOI: 10.1620/tjem.247.119
|View full text |Cite
|
Sign up to set email alerts
|

Renal Epithelioid Angiomyolipoma Undergoing Aggressive Clinical Outcome: The MDM2 Expression in Tumor Cells of Two Cases

Abstract: Epithelioid angiomyolipoma (EAML) has been known as a potentially malignant tumor which occasionally recur and/or metastasize to other organs, and clinically and pathologically recognized as distinct entity. However, the mechanisms of recurrence and/or metastasis (recurrence/metastasis) has still remained unknown. Here, we report two cases of renal EAML associated with recurrence/metastasis, and three cases of EAML in kidney or liver without recurrence/metastasis. According to the previous histological predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Inoue et al. 20 reported that the MDM2 protein was negative in primary EAML and showed a gradually increasing trend in two patients with metastasis or recurrence. These findings indicate the likelihood of new prognostic factors as treatment targets for EAML.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inoue et al. 20 reported that the MDM2 protein was negative in primary EAML and showed a gradually increasing trend in two patients with metastasis or recurrence. These findings indicate the likelihood of new prognostic factors as treatment targets for EAML.…”
Section: Discussionmentioning
confidence: 99%
“…18 Kenerson et al 19 found that the mTOR pathway was abnormally activated during the growth and progression of renal EAML; thus, the application of mTOR inhibitors such as rapamycin, everolimus, and others might lead to tumor reduction. Inoue et al 20 reported that the MDM2 protein was negative in primary EAML and showed a gradually increasing trend in two patients with metastasis or recurrence. These findings indicate the likelihood of new prognostic factors as treatment targets for EAML.…”
Section: Discussionmentioning
confidence: 99%
“…Several interesting studies relevant to this topic are discussed here. IHC evaluation revealed that MDM2 protein expression increased stepwise throughout every steps of metastasis/recurrence in the two cases of Renal Epithelioid Angiomyolipoma (EAML) studied, although it was negative in primary tumors [ 118 ]. This study suggests that MDM2 could play an important role in the recurrence/metastasis of renal EAML.…”
Section: Mdm2 (Hdm2) In Rccmentioning
confidence: 99%
“…MDM2 and chromosome 12 centromere (CEP12) using the Vysis LSI MDM2 Spectrum Orange Probe nd Vysis DNA FISH probe CEP12 (Abott Molecular/Vysis, Des Plaines, IL, USA) were examined, and. [ 13 ] results of MDM2-FISH showed focally positive and 5.96 of MDM2/CEP12 ratio, suggesting that MDM2 gene amplification indicated the lipomatous tumor as WDLS.…”
Section: Case Reportmentioning
confidence: 99%